Pemolisian dan Media: Dinamika Representasi dan Dampaknya pada Persepsi Publik - Kurniawan, Fajar; Ma’mur, Angghi Muliya; Cindrakasih, RR Roosita (Innovative: Journal Of Social Science Research, 2025)
Policing plays a key role in maintaining social order, but the representation of policing in mass and social media significantly shapes public perception of law enforcement officers. Positive coverage highlighting police success in ensuring security can enhance their image, while negative reports on police violence or abuse of power can damage public trust and worsen police-community relations. This article explores how mass and social media shape the representation of policing in Indonesia, examining its impact on public perception and police reform. The methodology used is qualitative research with a discourse analysis approach to media coverage in both mass and social media. This analysis aims to explore the narratives constructed by the media regarding policing and their influence on public opinion. Viral incidents of police violence on social media emphasize the critical role of media in demanding accountability and reform in the police system.